Characterization of biomass residue (yam peels) for bioethanol production - Bashir, Abdulrahman; Mohammed Baba, Nasirudeen; M. Akpomie, Timothy (International Journal of Advanced Chemistry, 2021)
The potential of yam peels for bioethanol production was investigated through an understanding of their compositional profile. The yam peels dried powder was subjected to X-ray diffraction analysis, and it was examined for proximate and biochemical composition. The result of the biochemical analysis of the yam peels showed the following: holocellulose (57.93 %) [cellulose (29.02 %) + hemicellulose (28.91 %)], and lignin (27.43 %), while the proximate analysis showed the following: moisture (11.11 %), ash (5.93 %), and volatile matter (68.4 %). Consequently, the X-ray diffraction pattern shows the presence of amorphous and crystalline region in the sample. The result showed that the yam peels possesses low lignin and high holocellulose content. This study indicate that the yam peels are potential candidates for bioethanol production. Â Â